Comparison of dna extraction methods for detection of citrus huanglongbing in colombia (2014)
Four DNA citrus plant tissue extraction protocols and three methods of DNA extraction from vector psyllid Diaphorina citri Kuwayama (Hemiptera: Psyllidae) were compared as part of the validation process and standardization for detection of huanglongbing (HLB). The comparison was done using several criterias such as integrity, purity and concentration. The best quality parameters presented in terms of extraction of DNA from plant midribs tissue of citrus, were cited by Murray and Thompson (1980) and Rodríguez et al. (2010), while for the DNA extraction from psyllid vectors of HLB, the best extraction method was suggested by Manjunath et al. (2008).